Numerical Analysis of Dynamic Properties of Nonlinear Rotor Systems of Aircraft Jet Engines - Ján Kamenický; Eduard Malenovský; Jaroslav Zapomel (International Journal of Rotating Machinery)
The paper deals with a manner of modelling and results of the calculation of dynamic properties and vibrations of the double spool aircraft turbofan engine AI-25, used in aeroplanes L-39 (Albatross). The calculations take into account the flexibilities of the engine's both coaxial rotors, their supports (including their hydrodynamic dampers), and its casing as well. Besides the short description of the engine design peculiarities and of its calculating model, there is also a short description of the used method of calculations, with focus on its peculiarities as well. Finally, some results of calculations and conclusions that follow from them are presented.